The Influence of Profitability, Firm Size, and Company Growth on Firm Value - Fidela Malva Kaulika; Imronudin Imronudin (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study investigates the influence of profitability, company size, and growth on firm value, with capital structure acting as a mediating factor. Utilizing a quantitative research design, the study focuses on manufacturing firms within the primary industry and chemical subsectors listed on the Indonesia Stock Exchange (IDX) for the year 2023. A purposive sampling technique was employed, and 30 companies were selected that met specific criteria that aligned with the study’s objectives. Profitability was measured using Return on Equity (ROE), while firm size was determined by total assets. Company growth was assessed based on the asset growth rate, and firm value was evaluated through the Price to Book Value (PBV) ratio. Data analysis combined descriptive statistics with classical assumption tests, including normality, multicollinearity, heteroscedasticity, and autocorrelation, followed by multiple linear regression. The findings indicate that ROE, company size and growth have a positive and significant impact on firm value. A higher ROE signifies efficient use of equity to generate profits, while larger company size and higher growth rates suggest improved stability and greater investor trust. The regression analysis showed a high degree of precision, as demonstrated by an adjusted R-square of 95.7%, indicating that the independent variables explain the majority of the variability in firm value. Additionally, the F-test confirmed that the combined effects of these independent variables significantly influence firm value. Ethical considerations, including data collection and analysis processes, were strictly followed to ensure the integrity of the study. Future research may also explore industry-specific characteristics in more detail, as they may affect the relationships between the variables differently across various sectors.